2004
DOI: 10.1111/j.1365-2095.2004.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary arginine requirement of fingerling Indian major carp, Cirrhinus mrigala (Hamilton)

Abstract: Dietary arginine requirement of fingerling Indian major carp, Cirrhinus mrigala (4.20 ± 0.05 cm; 0.60 ± 0.02 g) was determined by conducting a 8‐week feeding trial with casein–gelatine‐based diets (400 g kg−1 crude protein; 17.90 kJ g−1, gross energy), containing crystalline amino acids with graded levels of l‐arginine (10, 12.5, 15, 17.5, 20 and 22.5 g kg−1, dry diet). Fish were randomly stocked, in triplicate groups, in 55‐L indoor polyvinyl flow through circular tanks and fed experimental diets at 5% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
77
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(107 citation statements)
references
References 42 publications
26
77
4
Order By: Relevance
“…A similar tendency to that of whole-body was observed for muscle composition but protein content was not significantly different among treatments. These results are in agreement with previous studies on Indian major carp (Ahmed and Khan, 2004), black sea bream (Zhou et al, 2010) and H. fossilis (Khan and Abidi, 2011). Arginine is one of the most versatile amino acids and is a crucial precursor for protein synthesis (Wu and Morris, 1998).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A similar tendency to that of whole-body was observed for muscle composition but protein content was not significantly different among treatments. These results are in agreement with previous studies on Indian major carp (Ahmed and Khan, 2004), black sea bream (Zhou et al, 2010) and H. fossilis (Khan and Abidi, 2011). Arginine is one of the most versatile amino acids and is a crucial precursor for protein synthesis (Wu and Morris, 1998).…”
Section: Discussionsupporting
confidence: 94%
“…Also, considering the ability of teleostean fish to synthesize arginine from glutamate, the dietary glutamate content may affect the dietary arginine requirement estimation. Furthermore, Ahmed and Khan (2004) pointed out that the metabolic demands of the different pathways can interfere with the arginine requirement for protein synthesis, resulting in differences in arginine requirement level. Baker (1984) stated that increased growth performance in animals by dietary supplementation of an essential nutrient can be due to increased feed intake and/or metabolic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the experimental diets is given in Table 1. The levels of valine in the amino acid test diets were fixed on the basis of information available on other Indian major carps (Abidi & Khan 2004;Ahmed & Khan 2006;NRC 2011). To ensure maximum utilization of the limiting amino acid (Wilson 2002), the dietary protein level was fixed at 33%, which is lower than the optimum protein requirement (35%) of fingerling C. catla reported by Khan and Jafri (1991) and Dars et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…Valine requirements have been worked out for various fish species such as fingerling chinook salmon, Oncorhynchus tshawytscha (Chance et al 1964); fingerling channel catfish, Ictalurus punctatus (Wilson et al 1980); young Nile tilapia Oreochromis niloticus (Santiago & Lovell 1988); juvenile rainbow trout, O. mykiss (Rodehutscord et al 1997); fingerling rohu, Labeo rohita (Murthy & Varghese 1997;Abidi & Khan 2004); juvenile red sea bream, Pagrus major (Forster & Ogata 1998); fry Atlantic salmon, Salmo salar (Rollin 1999); fingerling mrigal, Cirrhinus mrigala (Benakappa & Varghese 2003, Ahmed & Khan 2006; adult rainbow trout, O. mykiss (Bae et al 2012); juvenile Jian carp, Cyprinus carpio (Dong et al 2013); and juvenile red sea bream, Pagrus major (Rahimnejad & Lee 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, arginine has been reported as an immunonutrient in high animal like humans, swine and rodents (Evoy et al, 1998), and proved to influence immune function in fish as well (Buentello et al, 2007). At present, arginine requirement studies in many kinds of commercial fish such as red drum (Sciaenops ocellatus) (Cheng et al, 2011), black sea bream (Sparus microcephalus) (Zhou et al, 2010), grouper (Epinephelus coioides) (Luo et al, 2007), mrigal (Cirrhinus mrigala) (Ahmed and Khan, 2004) have been reported.…”
Section: Introductionmentioning
confidence: 99%